Insights Into Spinal Dorsal Horn Circuit Function and Dysfunction Using Optical Approaches - Harding, Erika K.; Fung, Samuel Wanchi; Bonin, Robert P. (Frontiers in Neural Circuits, 2020)
Somatosensation encompasses a variety of essential modalities including touch, pressure, proprioception, temperature, pain, and itch. These peripheral sensations are crucial for all types of behaviours, ranging from social interaction to danger avoidance. Somatosensory information is transmitted from primary afferent fibres in the periphery into the central nervous system via the dorsal horn of the spinal cord. The dorsal horn functions as an intermediary processing center for this information, comprising a complex network of excitatory and inhibitory interneurons as well as projection neurons which transmit the processed somatosensory information from the spinal cord to the brain. It is now known that there can be dysfunction within this spinal cord circuitry in pathological pain conditions, and that these perturbations contribute to the development and maintenance of pathological pain. However, the complex and heterogeneous network of the spinal dorsal horn has hampered efforts to further elucidate its role in somatosensory processing. Emerging optical techniques promise to illuminate the underlying organization and function of the dorsal horn and provide insights into the role of spinal cord sensory processing in shaping the behavioural response to somatosensory input that we ultimately observe. This review will focus on recent advances in optogenetic and fluorescence imaging techniques in the spinal cord, encompassing findings from both in-vivo and in-vitro preparations. We will also discuss the current limitations and difficulties of employing these techniques to interrogate the spinal cord and current practices and approaches to overcome these challenges.